Development of an internalin-based double-antibody sandwich quantitative ELISA for the detection of Listeria monocytogenes in slaughterhouse environments - Cao, Qing; Shi, Wenjing; Wei, Yanquan; Wang, Jiayu; Wang, Zhonglong; Chong, Qian; Guo, Qianqian; Zhang, Kunzhong; Gai, Wenyan; Gou, Huitian; Xue, Huiwen (Frontiers in Veterinary Science, 2025)
IntroductionListeria monocytogenes causes zoonotic listeriosis with a high mortality rate, which is frequently detected in slaughterhouse processing environments and animal-based food. To enable the specific, rapid, and cost-effective detection of L. monocytogenes in environments and animal-based food, we developed a double-antibody sandwich quantitative ELISA (DAS-qELISA) method.MethodsThe method is based on monoclonal antibodies targeting internalin G (InlG), a surface protein of L. monocytogenes with demonstrated immunogenicity. The antibody pair 1D2-2H10 was selected for use in the sandwich ELISA format. Optimization of the DAS-qELISA method was carried out to determine its detection limits for InlG protein and L. monocytogenes.ResultsThe detection limits of the method were determined to be 32 ng/mg for the InlG protein and 7875.83 CFU/mL for L. monocytogenes. The accuracy of the method was evaluated across various bacterial concentrations, with results falling within 91.56–107.07% and a coefficient of variation (CV) of less than 10%. Compared to traditional methods, this approach requires only 12 h of bacterial enrichment and incubation to achieve 100% accuracy.DiscussionThe DAS-qELISA developed in this study provides a rapid, accurate, and cost-effective tool for the detection of L. monocytogenes in environmental and animal-based food samples. This method could be a valuable addition to current diagnostic approaches, offering quicker turnaround times and high accuracy for pathogen detection.